2016
DOI: 10.1177/0271678x16654492
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of glucose metabolism and metabolic connectivity by β-amyloid

Abstract: Glucose hypometabolism in the pre-clinical stage of Alzheimer's disease (AD) has been primarily associated with the APOE e4 genotype, rather than fibrillar b-amyloid. In contrast, aberrant patterns of metabolic connectivity are more strongly related to b-amyloid burden than APOE e4 status. A major limitation of previous studies has been the dichotomous classification of subjects as amyloid-positive or amyloid-negative. Dichotomous treatment of a continuous variable, such as b-amyloid, potentially obscures the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
5
22
0
Order By: Relevance
“…In agreement with our previous findings [21], our present results also suggest that the statistically significant association between A␤ deposition and glucose metabolism can only be detected across a heterogeneous population of subjects representing the continuous spectrum of the AD pathology, rather than in discrete segments of the AD progression trajectories represented by homogeneous subpopulations (e.g., CN, EMCI). As shown in Figure 2, statistically significant relationship between SVD-based A␤ and metabolism could be detected only in the LMCI subpopulation, perhaps due to the heterogeneity of the A␤ scores distribution across subjects (as shown in Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with our previous findings [21], our present results also suggest that the statistically significant association between A␤ deposition and glucose metabolism can only be detected across a heterogeneous population of subjects representing the continuous spectrum of the AD pathology, rather than in discrete segments of the AD progression trajectories represented by homogeneous subpopulations (e.g., CN, EMCI). As shown in Figure 2, statistically significant relationship between SVD-based A␤ and metabolism could be detected only in the LMCI subpopulation, perhaps due to the heterogeneity of the A␤ scores distribution across subjects (as shown in Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The different spatial patterns observed in the first eigenimage corresponding to the SVD analysis across the different cognitive subpopulations ( Supplementary Figure 1) are in agreement with previous studies suggesting that global fibrillar A␤ load and cerebral glucose metabolism follow spatiotemporally-divergent [10,13,15,21] evolution paths across AD progression. Indeed, our analysis showed that the bilateral angular gyri are common (across the three subpopulations) regions of strong reduced metabolism as revealed by the first FDG eigenimage, while they only have strong contribution to the A␤ eigenimage in the CN group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We expected adjacent brain regions to form clusters with high inter-cluster similarity for amyloid-β deposition (Figure 3), as it is known to have low variability in spatial distribution and, therefore, is often used as a dichotomic variable after applying a certain threshold to the global amyloid tracer uptake [Chételat et al, 2013, Landau et al, 2013 or as four-stage variable derived from a linear spreading pattern [Grothe et al, 2017, Sakr et al, 2019. We also found such clustering patterns for metabolism ( Figure 4) and gray matter volume ( Figure 5), matching previous studies on metabolism and gray matter covariance networks based on Pearson correlation [Yao et al, 2010, Carbonell et al, 2016, Pereira et al, 2016 or principal component analysis [Di and Biswal, 2012, Spetsieris et al, 2015, Savio et al, 2017. Clusters of high covariance have been found in the lateral and medial parietal lobe, lateral frontal lobe, and lateral and medial temporal lobe, and had been associated with simultaneous growth during brain development, functional co-activation, and axonal connectivity in the literature [Gong et al, 2012, Alexander-Bloch et al, 2013.…”
Section: Conditional Dependency Between Brain Regionssupporting
confidence: 89%
“…Nevertheless, the hypothesis has gained attention within the research field of Alzheimer's disease (AD), a dementia disorder neuropathologically characterized foremost by the presence of amyloid-␤ (A␤) plaques and neurofibrillary tangles (NFT) [14]. Interestingly, the disorder is also characterized by an early impaired glucose utilization and hypometabolism [15][16][17], which is associated with the A␤ 42 plaque burden [18]. Moreover, patients with AD commonly show an increased load of large abnormal aggregates of polysaccharides in astrocytes in form of polyglucosan bodies (PGB) or corpora amylacea [19][20][21].…”
Section: Introductionmentioning
confidence: 99%